“I’m afraid to eat a piece of toast”: The Lived Experience of Balancing Eating and Health Behaviors in Adults with Chronic Pain - Lindsay Flegge; Susan Glassburn; Amanda Wakefield; Kristina Bogdan; Crystal Tracy; Michelle Miller (Journal of Clinical Psychology in Medical Settings, 2026)
Abstract Chronic pain affects millions and is frequently comorbid with disordered eating behaviors; however, standard eating disorder screening tools often fail to capture the full scope of eating-related difficulties in this population. The purpose of this project was to explore the lived experience of eating problems among adults with complex chronic pain. Sixteen participants (15 women, age range 21–69, all White, non-Hispanic, cisgender) were interviewed by a member of the interprofessional research team, and data were analyzed using Reflexive Thematic Analysis. Participants described eating difficulties that extended far beyond traditional eating disorder criteria. Researchers constructed five overarching themes that represented the data: (1) Trapped in a Vicious Cycle (interplay of pain, medication side effects, mood, and maladaptive eating); (2) Living with Unpredictability and Trying to Manage Uncertainty (fear and trial-and-error surrounding food triggers); (3) Embodiment and Identity (profound shifts in body image, self-concept, and life trajectory); (4) Social Isolation (avoidance of social activities and perceived lack of understanding); and (5) Practical Barriers (financial, physical, and logistical obstacles to obtaining and preparing food). Findings show eating problems in chronic pain are complex, biopsychosocial phenomena characterized by fear-avoidance, impossible trade-offs, identity disruption, and systemic barriers rather than solely motivational or weight-related issues.